2019
DOI: 10.1101/687475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monosomes actively translate synaptic mRNAs in neuronal processes

Abstract: In order to deal with their huge volume and complex morphology, neurons localize mRNAs and ribosomes near synapses to produce proteins locally. A relative paucity of polyribosomes (considered the active sites of translation) detected in electron micrographs of neuronal processes (axons and dendrites)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 64 publications
(20 reference statements)
3
68
0
Order By: Relevance
“…However, very few polysomes have been observed in neuronal processes and monosomes are most populous in these compartments. Consistent with their high numbers, monosomes were shown to be important sources of translation in neuronal processes requiring protein production, as well as in synapses 54 . Further analysis revealed that certain transcripts show strong preferences for translation by either polysomes or monosomes.…”
Section: Rna Localization and Local Translation In Neuronsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, very few polysomes have been observed in neuronal processes and monosomes are most populous in these compartments. Consistent with their high numbers, monosomes were shown to be important sources of translation in neuronal processes requiring protein production, as well as in synapses 54 . Further analysis revealed that certain transcripts show strong preferences for translation by either polysomes or monosomes.…”
Section: Rna Localization and Local Translation In Neuronsmentioning
confidence: 82%
“…To tackle the first question, Biever et al used a ribosome footprinting approach to produce an unbiased list of mRNAs undergoing active translation in neuronal processes in vivo 54 . Similar to Cajigas et al, they isolated hippocampal neuropils containing both axons and dendrites.…”
Section: Rna Localization and Local Translation In Neuronsmentioning
confidence: 99%
“…It is widely accepted that actively translating mRNAs bind multiple ribosomes. However, this is contradicted by recent findings that translation occurs also on mRNAs bound to monosomes, and that translation is not directly proportional to the number of ribosomes on mRNA ( Requião et al, 2017 ; Neidermyer and Whelan, 2019 ; Biever et al, 2020 ). Relative to standard linear gradient of polysome profiling, non-linear gradients of RNC-seq (full-length translating mRNA sequencing) enable translating mRNAs elution at smaller volumes to circumvent the limitations of polysome profiling ( Liang et al, 2018 ).…”
Section: Narrow Sense Translatomicsmentioning
confidence: 68%
“…Despite evidence indicating that mature axons are capable of protein synthesis ( Kalinski et al, 2015 ; Rangaraju et al, 2017 ), the small size of axons and tight connections with glia and post-synapses have made in vivo transcriptome and translatome isolation extremely challenging. Importantly, microdissection-based approaches are limited to brain regions (e.g., the hippocampus; ( Biever et al, 2020 ) where axons are in separable lamina. While abundant transcriptome analysis demonstrated that the mRNAs for cAMP-response element binding protein (CREB), Na v 1.8, and other ion channels localize to DRG axons in vitro ( Thakor et al, 2009 ; Melemedjian et al, 2014 ; Hirai et al, 2017 ), there are technological challenges to research in which mRNAs are translated locally in nociceptor axons in vivo .…”
Section: Narrow Sense Translatomicsmentioning
confidence: 99%
“…According to literature, we found that both CHX and sBlock are able to stabilize AHA-peptides on ribosomes and polysomes (i.e. actively translating complexes) (Biever et al, 2020; Mathias et al, 1964). The efficiency to anchor polypeptides on ribosomes in CHX and sBlock treated cells was 50% higher compared to untreated cells, confirming that the drugs effectively stabilize nascent polypeptides (Fig.…”
Section: Resultsmentioning
confidence: 88%